Development of a Method for Testing a Powered Roof Support in Order to Determine its Operating Parameters - Trzop, Konrad Łukasz; Szurgacz, Dawid; Gil, Jan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Monitoring of powered roof supports is an area for research. External factors have a significant impact on the operation of powered support in a longwall excavation, therefore the use of solutions that will counteract these factors is an area for improvement. The article presents studies related to the adaptation of the measuring and recording system for the geometric parameters of the section and its compatibility with the powered roof support. Each of the presented stages consisted of a series of analyses based on computer simulations using the finite element method (FEM), as well as bench tests and real-life tests.
Keywords: geometry measurement; powered roof support; work safety; longwall mining; monitoring